Long-term dietary acid load is associated with depression in multiple sclerosis, but less evidence was found with fatigue and anxiety - Saul, A.; Taylor, B.V.; Blizzard, L.; Simpson-Yap, S.; Probst, Y.C.; Black, Lucinda; Ponsonby, A.L.; Broadley, S.A.; Lechner Scott, J.; van der Mei, I. (2023)
Background: Diet-dependent acid-base load has been associated with worsening in mental health, but to date no study has examined this in people with multiple sclerosis (PwMS). We examined the association between potential renal acid load (PRAL) and net endogenous acid production (NEAP) scores and depression, anxiety, and fatigue in PwMS. Methods: Participants with a first clinical diagnosis of CNS demyelination were followed prospectively as part of the AusLong Study (aged 18-59 years at cohort entry). At baseline, 5- and 10-year reviews, PRAL and NEAP scores were calculated using dietary intake in the preceding 12 months calculated from a food frequency questionnaire. At 5- and 10-year reviews, the Hospital Anxiety and Depression Scale was used to assess depression and anxiety, and the Fatigue Severity Scale assessed fatigue. Results: Higher PRAL and NEAP scores were associated with increased subsequent absolute value and change in HADS depression scores over five years’ follow-up (e.g., highest vs lowest PRAL quartile, 5-year change in HADS-D score: β=+3.01, 95%CI= 1.54, 4.48, p<0.001). The level of depression at the 10-year review was determined by both the baseline dietary acid scores and baseline-5-year changes in dietary acid scores (e.g., PRAL change from baseline to 5-year review, 10-year review HADS-D score: β=+0.09, 95%CI= 0.03, 0.15, p<0.001, NEAP change from baseline to 5-year review, 10-year review HADS-D score: β=+0.07, 95%CI= 0.01, 0.14, p=0.03). Some associations were observed with anxiety and fatigue but were much weaker and less consistent. Conclusion: Our findings indicate that a higher dietary acid load potentially has a long-term influence on the level of depression in PwMS. The evidence is less convincing for anxiety and fatigue.